2016
DOI: 10.15560/12.6.1998
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians of northwestern Buenos Aires province, Argentina: checklist, range extensions and comments on conservation

Abstract: Abstract:Northwestern Buenos Aires province is located within the Pampas region of Argentina. Agricultural practices have extensively modified native grasslands in a relatively short period, leaving no intact pristine areas. Based on data collected between 2006 and 2015 at 153 ponds in agricultural landscapes, we compiled an annotated list of the amphibians of northwestern Buenos Aires province. We report 13 extant species of amphibians, which represent 43% of the known amphibian diversity in Buenos Aires prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…In contrast, the present study showed that high values of amphibian diversity were associated with shallow constructed water habitats, with B. pulchella the only species strongly associated with deeper water. This can be explained by the fact that most amphibian species from the Pampean Region reproduce in temporary and semi‐permanent wetlands and low‐lying areas (Gallardo, 1974; Agostini et al, 2016). Moreover, the extensive formation of shallow temporary wetlands is typical of the region, as in most cases their water level depends on rainfall and phreatic discharges (Soriano, 1991; Viglizzo et al, 2009; Alsina, Nosetto & Jobbágy, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the present study showed that high values of amphibian diversity were associated with shallow constructed water habitats, with B. pulchella the only species strongly associated with deeper water. This can be explained by the fact that most amphibian species from the Pampean Region reproduce in temporary and semi‐permanent wetlands and low‐lying areas (Gallardo, 1974; Agostini et al, 2016). Moreover, the extensive formation of shallow temporary wetlands is typical of the region, as in most cases their water level depends on rainfall and phreatic discharges (Soriano, 1991; Viglizzo et al, 2009; Alsina, Nosetto & Jobbágy, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the region is characterized by an agricultural mosaic dominated by cattle grazing lands and croplands (Baeza & Paruelo, 2020). The change in land use introduced new artificial open water habitats that retain water and might offer, especially in times of drought, habitats for the development of amphibian populations (Agostini et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…El caso de Tillandsia recurvata es llamativamente similar a lo que ha ocurrido en la misma región con insectos (Farina, 2006;Nuñez Bustos, 2016), anfibios (Agostini & Roesler, 2011;Agostini et al, 2016), aves (Doiny Cabré, 2006Mac-Lean & Celsi, 2010) y mamíferos (Zamorano & Scillato Yané, 2008;Doumecq Millieu et al, 2012). También se halló una extensión similar en T. aeranthos (Loisel.)…”
Section: Discussionunclassified
“…La fauna de anfibios y reptiles de la provincia de Buenos Aires ha sido estudiada por Barrio (1962), Gallardo (1974;1977;1980;1987) y Williams (1991), entre otros. Se han estudiado en detalle las Sierras de los sistemas de Ventania (Koslowsky, 1896;Di Pietro, 2016) y de Tandilia (Vega y Bellagamba, 1990) en el centro-sur de la provincia, la Reserva Natural Otamendi (Pereira y Haene 2003) en el norte, los partidos del noroeste (Agostini, Saibene, Roesler, Bilenca, 2016), y la Costa Atlántica (Kacoliris, Horlent, Williams, 2006) en el este. La costa del Río de la Plata en el nordeste de la provincia de Buenos Aires se encuentra relativamente bien estudiada, aunque los trabajos existentes se enfocan al sector entre Punta Lara y Bahía Samborombón.…”
Section: Introductionunclassified